Impacts of climate change and urban growth on the streamflow characteristics of the Milwaukee River (Wisconsin, USA) - (:unkn) unknown (My University, 2017)
Hydrological impact studies of climate change increasingly take land use changes into account. However, the Midwestern USA is still understudied in this context. This study investigated the impacts of potential climate change and urban growth on the streamflow characteristics of the Milwaukee River located in southeastern Wisconsin. The Hydrological Simulation Program-Fortran (HSPF) was set up for the catchment and calibrated against observed streamflow data. The calibrated HSPF model was run with a series of climate and urban growth scenarios generated from nine global climate models (GCMs) and a land use simulation model, respectively. The outcomes from the GCMs, statistically downscaled at 10-km grid spacing, generally indicated a warmer and wetter climate by the mid-21st century, and the land use simulation model projected moderate urban growth by the time. Major findings from the study include: (1) land use changes alone resulted in negligible streamflow changes; (2) low flows showed more sensitivity than mean streamflow to climate change; (3) streamflow variability increased with both land use and climate changes, and (4) uncertainty in simulated streamflow among GCMs was larger than uncertainty among the GCM output themselves. The findings suggest that the current pace of urban growth would not pose much threat to the water resources in the area. Considering that low flow indices responded more sensitively than mean streamflow to climate change, measures to improve resilience to drought conditions are recommended. Because land use change impacts were quite small, considering the impact of both climate and land use scenarios did not produce a significantly different result.
Keywords: runoff; low flow; streamflow; climate change impact; urban growth